2018
DOI: 10.21834/e-bpj.v3i7.1265
|View full text |Cite
|
Sign up to set email alerts
|

An Appraissal of Independent Mobility towards Advancing Child-friendly Military Barrack Community Milieu in Developing Countries

Abstract: Independent mobility means children's opportunity of free play in the neighborhood without adult supervision. Meanwhile, mobility restriction has affected child environmental friendliness of military barrack community in developing countries including Nigeria. The aim of this study is to explore underlying parameters of independent mobility in advancing child-friendly barrack. Thirty journal articles in children's environment studies were reviewed and analyzed in relation to military geographies and its built … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In cluster #3, inclusive design, the top three keywords were independent mobility, public health, and travel. There is a strong correlation between the physical environment and independent mobility [52]. Studies in England [53], Australia [54], the United States [55], and Canada [56] have shown that children's independent mobility and active commuting have declined significantly in recent decades, particularly in downtown areas [57].…”
Section: Abstract Cluster Analysismentioning
confidence: 99%
“…In cluster #3, inclusive design, the top three keywords were independent mobility, public health, and travel. There is a strong correlation between the physical environment and independent mobility [52]. Studies in England [53], Australia [54], the United States [55], and Canada [56] have shown that children's independent mobility and active commuting have declined significantly in recent decades, particularly in downtown areas [57].…”
Section: Abstract Cluster Analysismentioning
confidence: 99%
“…Best practices on mobility across the globe have in recent times emphasized on vulnerable people but most developing countries lag behind. For example, Daodu & Said (2018) have observed that 70% of studies on the independent mobility of children between 2007 and 2008 were done in developed countries of Europe and little or nothing on Africa. In general, existing academic and technical discourses regarding motorization though numerous, have tended to be overly narrow and emanating from Engineers and economists (Klopp, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Best practices on mobility across the globe have emphasized on vulnerable people but most developing countries lag behind. For example, Daodu & Said (2018) have observed that 70% of studies on the independent mobility of children between 2007 and 2008 were done in developed countries of Europe and little or nothing on Africa. Current research on mobility in developing countries also shows a gap in articulating issues of automobile restrictions and the effects thereof.…”
Section: Conflicts In Use Of Space In Streets In Developing Countriesmentioning
confidence: 99%